IMPLEMENTASI MEDIA PEMBELAJARAN AUDIO VISUAL PADA PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR KELAS V SDN 060912 MEDAN DENAI - Sintya Nur Hikmayanti; Chairunnisa Amelia (STKIP Subang, 2024)
This study aims to describe the implementation of audio-visual learning media in Pancasila educational learning to improve student learning outcomes in class V SD N 060912 Medan Denai. The focus of this research is the learning outcomes of chapter 1